Procedural Justice and the Burden of Marital Dissolution in Contested Divorce Cases: Insights from Islamic Legal Philosophy - Gunawan, Gunawan; Budiwati, Anisah (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This research seeks to find a legal breakthrough in providing ease for ex-wives to obtain their rights due to divorce initiated by the husband in cases where the wife is the initiator. Understanding normatively the provisions that regulate the imposition of rights due to divorce on the ex-husband always poses difficulties for the ex-wife - not to say it is an impossible endeavor. However, from the perspective of Islamic legal philosophy, these regulations can lead to legal breakthroughs that provide ease for the ex-wife to obtain her rights. This research aims to explore legal breakthroughs that can be applied in judicial decisions to facilitate the former wife's access to her rights. With a normative and philosophical analysis approach, this research successfully discovered a legal breakthrough in the form of procedural justice that can be applied by judges in their rulings. The breakthrough consists of an addition to the dictum of the verdict that explicitly grants legitimacy to the authorized official who issues the divorce certificate, in this case, the court clerk, to withhold the ex-husband's divorce certificate until the ex-husband, who has been sentenced to fulfill the rights resulting from the divorce for the ex-wife, has actually fulfilled his obligations.